Salmonella typhimurium LT2 Catabolizes Propionate via the 2-Methylcitric Acid Cycle - Horswill, Alexander R. (American Society for Microbiology, 1999)
We previously identified the prpBCDE operon, which encodes catabolic functions required for propionate catabolism in Salmonella typhimurium. Results from (13)C-labeling experiments have identified the route of propionate breakdown and determined the biochemical role of each Prp enzyme in this pathway. The identification of catabolites accumulating in wild-type and mutant strains was consistent with propionate breakdown through the 2-methylcitric acid cycle. Our experiments demonstrate that the α-carbon of propionate is oxidized to yield pyruvate. The reactions are catalyzed by propionyl coenzyme A (propionyl-CoA) synthetase (PrpE), 2-methylcitrate synthase (PrpC), 2-methylcitrate dehydratase (probably PrpD), 2-methylisocitrate hydratase (probably PrpD), and 2-methylisocitrate lyase (PrpB). In support of this conclusion, the PrpC enzyme was purified to homogeneity and shown to have 2-methylcitrate synthase activity in vitro. (1)H nuclear magnetic resonance spectroscopy and negative-ion electrospray ionization mass spectrometry identified 2-methylcitrate as the product of the PrpC reaction. Although PrpC could use acetyl-CoA as a substrate to synthesize citrate, kinetic analysis demonstrated that propionyl-CoA is the preferred substrate.